Modifikasi Kompor Biomassa dengan Penambahan Pengumpan Bahan Bakar dan Pengatur Nyala Api - Dwi Sapta Nofrizal; Mukhlisin Matkur Kalam; Ade Pratama; Imam Sofi’i; Tutu Petrus Basuki (Jurusan Teknologi Pertanian, 2013)
Utilizing of biomass simple stove with high efisien intense be needed in order to be used widely society so far. Chaff stove ussualy used is not perfectly is lack and necessary to make perfect. Objective this research to modified chaff stove and test performance by getting compare with before and after modified used different material. Method used by the way modified chaff stove now add material feeder, regulator flame and feeder flame. The result indicate that the initial time light a fire until normally for chaff stove modified is longer than before modified, the end of temperature for chaff stove modified better than before modified, but chaff stove modified necessary increment with blower. On the use of coconut shell material, chaff stove modified more smoke because deficiency in oxygen, however use other material e.g chaff and sawdust is better. Keywords: chaff stove, modified